A Novel Cathode Architecture Using Ordered Pt Nanostructure Thin Film for AAEMFC Application. (1st December 2016) - Jia, Jia; Yu, Hongmei; Gao, Xueqiang; Fu, Li; Chi, Jun; Song, Wei; Yi, Baolian; Shao, Zhigang
Abstract: A novel cathode architecture using vertically aligned Co-OH-CO3 nanoneedle arrays as ordered catalyst support for AAEMFC application is developed. Co-OH-CO3 nanoneedle arrays are directly grown on a stainless steel sheet via hydrothermal reaction. A Pt nanosturcture thin film is prepared on the surface of Co-OH-CO3 by sputter deposition to form Pt/Co-OH-CO3 nanoneedle arrays and the thickness of the Pt nanostructure thin film is only several nanometers. After transferring the Pt/Co-OH-CO3 nanoneedle arrays on an alkaline anion exchange membrane by hot pressing and acid washing, the novel cathode catalyst layer is formed, with the thickness of several hundred nanometers. Without alkaline ionomer in the cathode catalyst layer and the AAEMFC with the prepared MEA shows a peak power density of 113 mW cm −2 with ultra-low Pt loading down to 20 μg cm −2 . This is the first time that order-structured electrode architecture is applied in the AAEMFC, which can deliver higher power density without alkaline ionomer than the conventional MEA with the same Pt loading.